CUSTOMER LOYALTY: The Effect Customer Satisfaction, Experiential Marketing and Product Quality - Gunawan, Ian (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2022)
Tight competition requires companies to be able to do more, so that customer loyalty is maintained. However, the efforts made are not easy, companies need to mobilize all available resources, especially those directly related to consumer behavior. In customer theory, providing satisfaction is one of the main keys to the birth of loyalty behavior. Based on this phenomenon, this research seeks to obtain information through scientific testing with a measurable method, in the form of a quantitative approach. The research correspondents are Uniqlo consumers, totaling 100 people. How to collect data in this study by distributing questionnaires purposively. The results of the study suggest that the best path analysis model in increasing customer loyalty is to focus on increasing customer satisfaction. This becomes rational, because the customer in making a purchase decision is strongly influenced by his psychological state, and with a feeling of satisfaction, loyal behavior will be formed.